1992
DOI: 10.1111/j.1479-828x.1992.tb01905.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Obesity on the Outcome of Successful Surgery for Genuine Stress Incontinence

Abstract: In a study of 190 patients with genuine stress incontinence, 91 patients were of normal weight, 66 overweight and 33 obese as determined by their Body Mass Index at the time of operation which was either a colposuspension (143) or a silastic sling insertion (47). Body mass index was found to significantly alter the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 7 publications
2
24
1
2
Order By: Relevance
“…Other authors have noted an increased failure rate of stress incontinence surgery in women who were overweight 27 . In our study, although there was no difference in the success rate between normal or overweight women and obese (with a body mass index over 30), there were wide confidence intervals.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have noted an increased failure rate of stress incontinence surgery in women who were overweight 27 . In our study, although there was no difference in the success rate between normal or overweight women and obese (with a body mass index over 30), there were wide confidence intervals.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that morbidly obese women with USI can undergo operations for this disorder with a good chance for success, and that the sling operation may be the procedure of choice for this population. Brieger and Korda [2] reported an increased failure rate among obese women who underwent bladder neck needle suspension and retropubic procedures. O'Sullivan et al [3] demonstrated poor outcomes in obese women who underwent needle suspension.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of obesity on the outcome of surgical treatment is unclear. While some authors report high failure and postoperative complication rates [2,3], others do not consider obesity to be a risk factor with regard to failure or surgical complications [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Le tableau proposé par Cummings et Rodning [13] rapporte les taux de succès parmi les travaux publiés [13][14][15][16][17] dans les années 1980-1990, avec le plus souvent des cohortes de faibles effectifs (Tableau 4).…”
Section: Iu Et Obésitéunclassified